2013
DOI: 10.1002/app.39283
|View full text |Cite
|
Sign up to set email alerts
|

Controllable preparation, rheology, and plugging property of micron‐grade polyacrylamide microspheres as a novel profile control and flooding agent

Abstract: A series of micron-grade polyacrylamide microspheres were prepared by inverse suspension polymerization of acrylamide (AM) and N,N 0 -methylene bisacrylamide (MBA) in oil phase, with Span80 and Tween80 as dispersion stabilizers, and ammonium persulfate (APS) as an initiator. The conversion rate and coagulum rate were introduced to optimize the inverse suspension polymerization conditions of micron-grade polyacrylamide microspheres. The swelling property of polyacrylamide microspheres in aqueous solution and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 9 publications
(7 reference statements)
0
40
0
Order By: Relevance
“…In this sense, it is necessary to guarantee that polymeric spheres have stability in the reservoir under harsh conditions. Literature has reported that the loss of the stability of the polymeric spheres is influenced by aspects such as the stabilizer content and the ratio between the components of the polymeric system . For this reason, the purpose of this section is to investigate the effect of the removal of the oil phase and stabilizers of the polymeric spheres on the system stability, the results are exhibited in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it is necessary to guarantee that polymeric spheres have stability in the reservoir under harsh conditions. Literature has reported that the loss of the stability of the polymeric spheres is influenced by aspects such as the stabilizer content and the ratio between the components of the polymeric system . For this reason, the purpose of this section is to investigate the effect of the removal of the oil phase and stabilizers of the polymeric spheres on the system stability, the results are exhibited in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Yao et al . reported the synthesis of polymeric spheres by inverse suspension polymerization of acrylamide (AM) and N,N'‐methylene bisacrylamide (MBA) in the oil phase, with Span80 and Tween80 as dispersion stabilizers, and ammonium persulfate (APS) as an initiator …”
Section: Introductionmentioning
confidence: 99%
“…The slowly swelling properties prevent artificially high injection pressure from damaging to the formation. Recent researches have been carried out on the profile control mechanism of microspheres [8][9][10]. Slow swelling rate of microspheres avoids blocking in the zone close to the wells and increases core injectivity [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylamide or acrylamide copolymer crosslinked microspheres used for reducing water cut to increase oil recovery have received extensive interest. The aspects of concern include the preparation, plugging performance, profile control performance, stability, mechanism of transport in porous media and so on.…”
Section: Introductionmentioning
confidence: 99%